Natural variations of chlorophyll fluorescence and ion transporter genes influenced the differential response of japonica rice germplasm with different salt tolerances - Song, Jiawei; Yang, Hui; Qiao, Chengbin; Zhu, Chunyan; Bai, Tianliang; Du, Huaidong; Ma, Shuaiguo; Wang, Na; Luo, Chengke; Zhang, Yinxia; Ma, Tianli; Li, Peifu; et al. (Frontiers in Plant Science, 2023)
Soil salinity seriously restricts rice growth, development, and production globally. Chlorophyll fluorescence and ion content reflect the level of injury and resistance of rice under salt stress. To understand the differences in the response mechanisms of japonica rice with varying degrees of salt tolerance, we analyzed the chlorophyll fluorescence characteristics and ion homeostasis of 12 japonica rice germplasm accessions by comprehensive evaluation of phenotype, haplotype, and expression of salt tolerance-related genes. The results revealed that salt-sensitive accessions were rapidly affected by the damage due to salinity. Salt tolerance score (STS) and relative chlorophyll relative content (RSPAD) were extremely significantly reduced (p<0.01), and chlorophyll fluorescence and ion homeostasis were influenced by various degrees under salt stress. The STS, RSPAD, and five chlorophyll fluorescence parameters of salt-tolerant accessions (STA) were significantly higher than that of salt-sensitive accessions (SSA). Principal component analysis (PCA) with 13 indices suggested three principal components (PCs), with a cumulative contribution rate of 90.254%, which were used to screen Huangluo (typical salt-tolerant germplasm) and Shanfuliya (typical salt-sensitive germplasm) based on the comprehensive evaluation D-value (DCI). The expression characteristics of chlorophyll fluorescence genes (OsABCI7 and OsHCF222) and ion transporter protein genes (OsHKT1;5, OsHKT2;1, OsHAK21, OsAKT2, OsNHX1, and OsSOS1) were analyzed. The expressions of these genes were higher in Huangluo than in Shanfuliya under salt stress. Haplotype analysis revealed four key variations associated with salt tolerance, including an SNP (+1605 bp) within OsABCI7 exon, an SSR (−1231 bp) within OsHAK21 promoter, an indel site at OsNHX1 promoter (−822 bp), and an SNP (−1866 bp) within OsAKT2 promoter. Variation in OsABCI7 protein structure and differential expression of these three ion-transporter genes may contribute to the differential response of japonica rice to salt stress.